2009
DOI: 10.1590/s0102-311x2009001400005
|View full text |Cite
|
Sign up to set email alerts
|

Práticas contraceptivas e iniciação sexual entre jovens de três capitais brasileiras

Abstract: IntroduçãoAs práticas contraceptivas na iniciação sexual são diversificadas entre países, sobretudo naqueles em que se assegura o fornecimento dos insumos. Contudo, mesmo isso não exclui desigualdades entre grupos sociais e diferenças no interior destes 1 .Nos países desenvolvidos e em desenvolvimento, a maioria dos jovens tem sua primeira relação sexual antes dos 20 anos, grande parcela antes dos 18, constatando-se historicamente a tendência à diminuição da idade e das diferenças entre as experiências de home… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
14

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 13 publications
(32 reference statements)
0
7
0
14
Order By: Relevance
“…A study in three Brazilian capitals showed that girls tend to initiate sex in their relationships with greater stability and a little later. Have the boys start earlier and in eventual relationships 29 . The associations of sex without protection with low maternal school education, studying at a public school, working and the races/skin colors black, indigenous and yellow indicate social inequality in the exposure to this risk behavior among adolescents in the country .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study in three Brazilian capitals showed that girls tend to initiate sex in their relationships with greater stability and a little later. Have the boys start earlier and in eventual relationships 29 . The associations of sex without protection with low maternal school education, studying at a public school, working and the races/skin colors black, indigenous and yellow indicate social inequality in the exposure to this risk behavior among adolescents in the country .…”
Section: Discussionmentioning
confidence: 99%
“…In a population study on sexual, contraceptive and reproductive behavior of 2,991 women from 15 to 20 years in the National Demographic and Health Research of Children and Women, in 2006 , the poorest and least educated adolescents had more unprotected behavior, i.e., lowest percentage of contraceptive use at the first intercourse and at current use when compared to youngsters in better social conditions 14 . In Brazil, teenage pregnancy is related to lower family income, school dropout in primary education for both gender and higher possibility to perform abortions 14,29,30 . Moreover, early integration at work may induce maturity and the adoption of adult roles prematurely, besides reinforcing unhealthy behaviors and even stimulating the formation of a new family 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Ao mesmo tempo em que lhe permite adentrar em um mundo de novas descobertas, pode inseri-lo em um grupo de vulnerabilidade a doenças sexualmente transmissíveis (DST) e aids. Essa inserção pode ter como desfecho, também, a ocorrência de gravidez na adolescência, aborto e outros problemas de ordem biológica, socioeconômica e psicológica 12,13,14,15,16 .…”
Section: Introductionunclassified
“…Ao mesmo tempo em que lhe permite adentrar em um mundo de novas descobertas, pode inseri-lo em um grupo de vulnerabilidade a doenças sexualmente transmissíveis (DST) e aids. Essa inserção pode ter como desfecho, também, a ocorrência de gravidez na adolescência, aborto e outros problemas de ordem biológica, socioeconômica e psicológica 12,13,14,15,16 .Identificam-se na literatura estudos que enfatizam o tema, fazendo uma forte relação entre o comportamento adotado na ocasião da primeira relação sexual e práticas que podem perdurar por toda a vida do indivíduo, em especial quanto ao uso do preservativo 17,18,19 . Também é possível identificar uma associação entre início da vida sexual por indivíduos muito jovens e o fator de risco para a aquisição de DST e gravidez na adolescência 14,20 .…”
unclassified
See 1 more Smart Citation